Confirmation of local anesthetic distribution by radio‐opaque contrast spread after ultrasound guided infraclavicular catheters placed along the posterior cord in children: a prospective analysis. Issue 3 (21st October 2014) - Ponde, Vrushali; Shah, Dipal; Johari, Ashok; Lonnqvist, Per‐Arne
Summary Background The needle tip placed at the level of posterior cord under ultrasound guidance is described as the most effective way to obtain single shot successful block in adults, for forearm and hand surgeries. Objective The aim of this research was to study the spread of dye (depicting the local anesthetic) through catheters placed along the posterior cord. This was performed with continuous infraclavicular blocks placed under ultrasound guidance in children. Methods Twenty‐four ASA 1 and 2 children, aged 7 months to 8 years old, scheduled for upper limb orthopedic surgeries were included in this prospective descriptive study. They received continuous infraclavicular block under ultrasound guidance. Skin markings were obtained from catheters that were placed below the posterior cord inserted 2–3 cm beyond the tip of the Tuohy needle. A radio‐opaque dye was injected into the catheters and 5 min later, the dye spread was evaluated fluoroscopically. Postoperatively, all patients received a continuous infusion of 0.125% bupivacaine for pain relief. Results All 24 cases showed the presence of the dye along the neurovascular bundle in the infraclavicular region suggesting successful blocks. The mean ± standard deviation of the skin marking for the catheter was 5.61 ± 1.77 cm. Postoperatively, all patients had adequate pain relief with the catheters. One patient had break through pain on day 1 and four catheters were accidentally dislodged on day 2. Conclusion We conclude that continuous infraclavicular catheters can be accurately and effectively placed along the posterior cord exclusively under ultrasound guidance in infants and small children.